(untitled) (Международный научный журнал «Инженер», 2026)
Soil-containing cannabis accounts for more than 65 percent of the available channels in our country today. 25-30% of water resources are lost in vain precisely as a result of filtration in soil-containing cannabis. In order to conserve water resources, maintain environmental sustainability, a number of important tasks have been set by the government to prevent filtration in canals. The article cited the analysis of the results of scientific research carried out to prevent filtration processes in the channels. To prevent the filtration process, the possibilities of using a composite polymer coating obtained from domestic raw materials, used car tires were considered. The results obtained are comparable to existing technologies.